Comparative Analysis of Data Consolidation in Surveillance Networks - Павлова, Д. Б.; Заволодько, Г. Е.; Обод, І. І.; Свид, І. В.; Мальцев, О. С.; Сайківська, Л. Ф. (DESSERT, 2019)
In the paper, on ground of comparative analysis of the data consolidation methods in the stages of tertiary data processing, primary data processing and signal data processing in a unified information network of airspace surveillance systems for air objects, it was shown that the most effective is the joining of decisions about air objects at the stage of signal data processing, which provides the greatest probability of information provision for consumers of the airspace control system.
Keywords: information network of surveillance systems; processing and consolidation of surveillance data